Perception of Trainees about Gender Sensitization in Agriculture (Indian Journal of Extension Education, 2012)
ANational Gender Resource Centre in Agriculture (NGRCA) was set up in the Department of Agriculture & Cooperation th (DAC), MoAduring 10 Five Year Plan. It is a modal centre for convergence and coordination of gender-related issues at national level. In order to create adequate sensitivity among the programme implementers (at three different levels, viz. senior level, middle level and cutting edge level) and to facilitate them to perceive and implement agricultural schemes/programmes with greater gender focus. Bihar Agricultural Management and Extension Training Institute (BAMETI) has given responsibility to organize 10 training programmes for the delivery on gender sensitization modules for the cutting edge field level functionaries of agriculture and allied departments. The BAMETI has developed a pre training questionnaire related to attitude, knowledge, behaviour and skill towards gender for analysis of perception of trainees about gender sensitization and issues in agriculture. Training programmes based on gender sensitization were found an effective tool to motivate the cutting- edge extension functionaries.